AB1058 Is hepatitis b surface antigen (HBSAG) enough alone as a screening test for hbv infection in rheumatic disease patients before starting immunosuppressive therapies?. (12th June 2018) - Abdel Noor, R.A.; Watany, M.; Abd-Elsalam, S.; Elkhalawany, W.; Soliman, S.; Badawi, R.
Abstract : Background: Prevalence of hepatitis B virus in patients with rheumatic diseases has been reported differently among studies. The loss of immune control in these patients may result in the reactivation of HBV replication within hepatocytes. Considering the lifelong use of multiple anti-rheumatic drugs, screening for HBV is recommended before starting immunosuppressive or immunomodulatory therapy. Objectives: The aim of this study was to select the best and simplest test for screening of HBV in rheumatic patients in Egypt. Methods: This cross sectional study was carried out on 102 patients with different rheumatic diseases. Screening to all patients by hepatitis B surface antigen (HBsAg), hepatitis C virus (HCV) and human immune deficiency virus antibodies (HIV) were done. HBV core antibodies and real time PCR to detect HBV DNA were done. Results: The mean age of the patients was 37.18%±12.37. 3.9% of them were males and 96.1% were females. We found that HBsAg was positive in two patients (2%) and negative in 100 patients (98%). HBcAb was positive in 24 patients (23.5%) and negative in 78 patients. however PCR for hepatitis B DNA was positive in 2 patients (2.0%) only who were positive for both HBsAg and HBC Ab. HBsAg had 100% Sensitivity, 100% Specificity, 100% PPV, 100% NPV and 99.0% accuracy. While antiHBc had 100% Sensitivity, 78% Specificity, 8% PPV, 100% NPV and 78% accuracy in screening of HBV. Conclusions: We can conclude that screening for hepatitis B virus is essential for all patients with rheumatic diseases before starting therapies either steroids, immunosuppressive therapies or biologics. For financial issues especially in developing countries screening by HBsAg may be enough as an initial test especially if non biological therapies are used as it is superior to anti HBc for screening for HBV infection. References: [1] Raimondo G, Allain J-P, Brunetto MR, Buendia M-A, Chen D-S, Colombo M, et al. Statements from the Taormina expert meeting on occult hepatitis B virus infection. Journal of hepatology. 2008;49(4):652–7. [2] Harigai M, Mochida S, Mimura T, Koike T, Miyasaka N. A proposal for management of rheumatic disease patients with hepatitis B virus infection receiving immunosuppressive therapy. Modern rheumatology. 2014;24(1):1–7. [3] Karadağ Ö, Kaşifoğlu T, Özer B, Kaymakoğlu S, Kuş Y, İnanç M, et al. Viral hepatitis screening guideline before biological drug use in rheumatic patients. European Journal of Rheumatology. 2016;3(1):25. Disclosure of Interest: None declared